2022
DOI: 10.1038/s41598-022-05656-3
|View full text |Cite
|
Sign up to set email alerts
|

The gut virome in two indigenous populations from Malaysia

Abstract: The human gut contains a complex microbiota dominated by bacteriophages but also containing other viruses and bacteria and fungi. There are a growing number of techniques for the extraction, sequencing, and analysis of the virome but currently no standardized protocols. This study established an effective workflow for virome analysis to investigate the virome of stool samples from two understudied ethnic groups from Malaysia: the Jakun and Jehai Orang Asli. By using the virome extraction and analysis workflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Siphoviridae, the most dominant viral family of the normal human gut viral community (Zuo et al, 2020;Tomofuji et al, 2021;Lee et al, 2022), was found to be less distributed in the gut virome of PCOS patients than in that of controls. Siphoviridae is a type of double-stranded DNA (dsDNA) virus that is known to be rich in temperate phages and infects a wide range of gut bacteria, such as Bacillus, Enterococcus, Clostridium, Streptococcus, Lactobacillus, and Escherichia (Sekulovic et al, 2014;Adriaenssens et al, 2015;Chehoud et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Siphoviridae, the most dominant viral family of the normal human gut viral community (Zuo et al, 2020;Tomofuji et al, 2021;Lee et al, 2022), was found to be less distributed in the gut virome of PCOS patients than in that of controls. Siphoviridae is a type of double-stranded DNA (dsDNA) virus that is known to be rich in temperate phages and infects a wide range of gut bacteria, such as Bacillus, Enterococcus, Clostridium, Streptococcus, Lactobacillus, and Escherichia (Sekulovic et al, 2014;Adriaenssens et al, 2015;Chehoud et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Amplicon-based sequencing of the internal transcribed spacer or the 18S rRNA genes can be useful to characterize the eukaryotic members of the microbiome, but is also limited in terms of taxonomic resolution, is targeted to specific components of the microbiome, and has significant challenges given the evolutionary proximity of the eukaryotic components of the microbiome with the organisms harbouring the microbiome (Hu et al , 2015; Popovic et al , 2018; Campo et al , 2019). In the case of RNA and DNA viruses, non-amplicon-based metatranscriptomics and metagenomics are necessary, in particular for the genomic discovery and characterization of highly variable viruses in the microbiome (Dheilly et al , 2022; Lee et al , 2022).…”
Section: Where To Next?mentioning
confidence: 99%
“…As viruses are "our third genome", looming behind the bacterial "second genome", researchers turned to virome analyses in IBD to gain complementary insights into the pathogenesis of IBD beyond microbiota, genetics, immunological and environmental risk factors. A comprehensive study was published [35] . The researchers started with metagenome sequencing of stool filtrates for 18 Crohn's disease (CD) and 42 UC patients and compared them with stools from 12 non-IBD household controls.…”
Section: Virome Research In Ibdmentioning
confidence: 99%